Optical tweezers to measure the elasticity of red blood cells: a tool to study the erythrocyte response to antimalarials - Dorta, Doriana; Padmore, Patrick; Correa, Ricardo; Pineda, Laura; Spadafora, Carmenza; Sarmiento-Gómez, Erick; Coronado, Lorena M. (Frontiers in Malaria, 2024)
The Plasmodium falciparum parasite infected more than 240 million people and killed around six hundred thousand patients last year alone. A key aspect of the pathophysiology of P. falciparum is the increased rigidity and adhesiveness of the membrane of infected red blood cells (iRBC). Optical tweezers (OT) have been proposed as a tool for evaluating and screening potential drugs because they can provide valuable information to determine a drug's mechanism of action. The OT experimental design of this study was used to compare the plasma membrane stiffness of uninfected RBCs (uRBCs) and iRBCs, showing that the iRBCs were 4 times more rigid. The increased rigidity was more evident in those RBCs infected by the P. falciparum schizont stage. We also characterized the membrane deformability of iRBCs in vitro under the active concentration of common antimalarials on drugresistant and non-drug-resistant P. falciparum strains. In addition, we also determined that the increased membrane rigidity of uRBCs during P. falciparum infection, known as the bystander effect, is partially reversed by antimalarial drugs. These findings suggest that single-cell mechanical measurements have potential uses in personalized medicine by characterizing the response to malaria treatment.